The Tenses and Aspects in the Three Novel CoronaVirus-19 Songs - Britni Delfita Pata Allo K; Dewi Nuryanti (Talenta Publisher, 2022)
Abstract. This research is aimed to explain the tense and aspects that are used in the lyrics of The Three Novel CoronaVirus-19 Songs. It is also aimed to explain the messages in these songs. The data are taken from the three singers' Youtube Videos. The method used in this research is a qualitative method. The analysis of the data is using theory by John. I. Saeed (2003) and Charles W. Kreidler (1998). The results of this research found that tenses in lyrics show the different situations of the verbs; the use of the verbs shows the process of both actions that have their focus on beginning and ending. Meanwhile, the aspects in the lyrics show that the lyrics have a completion or ongoing events. The messages conveyed by the song are to remind people of the dangerous situation of the virus, to tell people to have awareness of the situation and get closer to their family, and to persuade people to get more sensitive to their surroundings and do whatever they can do to others. Keyword: Tense, aspect, Situations, Covid-19, Songs Abstrak. Penelitian ini ditujukan untuk menjelaskan tentang kala dan aspek dalam tiga lagu bertema The Novel CoronaVirus-19. Tujuan lainnya adalah untuk menjelaskan pesan yang terkandung dalam ketiga lagu tersebut. Data diambil dari kanal Youtubepenyanyi setiap lagu. Teori John I Saeed (2003) dan Charles W. Kreidler (1998) digunakan dalam menganalisis data. Metode yang digunakan dalam analisis ini adalah metode Kualitatif. Analisis data menemukan bahwa kala dalam lirik lagu menunjukkan perbedaan situasi verba, proses yang terkandung dalam penggunaan verba pada lagu ini menunjukkan adanya fokus kegiatan pada permulaan dan akhir kegiatan. Sementara aspek yang terkandung dalam lirik lagu-lagu ini menunjukkan bahwa peristiwa tutur yang terjadi merupakan peristiwa tutur yang sedang berlangsung dan selesai.Pesan yang disampaikan lewat ketiga lagu adalah mengingatkan bahaya penyebaran virus, mengingatkan semua orang untuk lebih peka pada situasi covid-19 dan lebih dekat dengan keluarga, serta mengajak semua orang untuk lebih sensitif terhadap lingkungan sekitarnya dan dapat melakukan apapun bagi sesamanya. Kata Kunci: Kala, Aspek, Situasi, Covid-19, Lagu